2022
DOI: 10.3389/fimmu.2022.979675
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in research on oxidative stress associated with periodontitis from 1987 to 2022: A bibliometric analysis

Abstract: BackgroundOxidative stress has been implicated in many chronic inflammatory diseases, including periodontitis. To date, however, only a few bibliometric analyses have systematically studied this field. This work sought to visualize research hot spots and trends in oxidative stress associated with periodontitis from 1987 to 2022 through bibliometric approaches.MethodsThe Web of Science Core Collection was searched to retrieve relevant publications. HistCite, VOSviewer, and CiteSpace were used to perform bibliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In addition, lipopolysaccharides have been suggested as a molecular link between periodontal microbiota and cardiometabolic diseases [31] . Oxidative stress is conducive to periodontal tissue destruction, and periodontitis may promote the progression of kidney diseases, diabetes, and cardiovascular diseases through oxidative stress [32] . In contrast, antioxidant drugs can reduce ROS levels and alveolar bone loss caused by periodontitis [33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lipopolysaccharides have been suggested as a molecular link between periodontal microbiota and cardiometabolic diseases [31] . Oxidative stress is conducive to periodontal tissue destruction, and periodontitis may promote the progression of kidney diseases, diabetes, and cardiovascular diseases through oxidative stress [32] . In contrast, antioxidant drugs can reduce ROS levels and alveolar bone loss caused by periodontitis [33] .…”
Section: Discussionmentioning
confidence: 99%
“…[31] Oxidative stress is conducive to periodontal tissue destruction, and periodontitis may promote the progression of kidney diseases, diabetes, and cardiovascular diseases through oxidative stress. [32] In contrast, antioxidant drugs can reduce ROS levels and alveolar bone loss caused by periodontitis. [33] KEGG enrichment analysis showed that these targets were mainly enriched in 163 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometrics, defined by Alan Pritchard in 1969, can integrate retrospective information effectively, search correlations of data, and predict future trends for scholars [ 19 , 20 ]. Over the past decades, bibliometric analyses have been widely applied to medical research, such as research on PD [ 21 ], cardiovascular and cerebrovascular diseases [ 22 ], cancer [ 23 ], and metabolic diseases [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It collected data on various entities (e.g., countries, institutions, journals) to nd out the hidden associations and facilitate understanding the research eld at a broader level [13]. This method had been used in several medical research to predict hotspots, review results and guide clinical therapy [14,15,16]. In the eld of ischemic stroke, it provides valuable reference for further study.…”
Section: Introductionmentioning
confidence: 99%